2021
DOI: 10.1021/acs.orglett.0c03976
|View full text |Cite
|
Sign up to set email alerts
|

Cooperation of Cis Vicinal Acceptors for Donor–Acceptor Cyclopropane Activation: TfOH-Promoted Ring-Opening/Aryl Shift Rearrangement to 3- and 5-Ylidenebutenolides

Abstract: A convenient route to 3- and 5-ylidenebutenolides from readily available cis-2-acylcyclopropane-1-carboxylates is described. Upon exposure to TfOH, synergistic activation of the vicinal acceptors in cis-2-acylcyclopropane-1-carboxylates generates highly strained bicyclic oxocarbenium ion intermediates, which undergo the ring-opening/aryl shift/deprotonation cascade process to form the 3- or 5-ylidenebutenolides depending on the acyl group. On the other hand, the corresponding trans isomers, from which it is di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
16
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 61 publications
0
16
1
Order By: Relevance
“…2-Methoxyphenyl or 3-bromo-4-methoxyphenyl groups are not electron-rich enough for this transformation, which gave the 3-ylidenebutenolides as reported previously. 6 In addition to the structural confirmation of 8a referring to the literature, 1f the structure of 8n (CCDC No. : 2083287) was further confirmed by single-crystal X-ray crystallography.…”
Section: Accepted Manuscriptmentioning
confidence: 99%
See 4 more Smart Citations
“…2-Methoxyphenyl or 3-bromo-4-methoxyphenyl groups are not electron-rich enough for this transformation, which gave the 3-ylidenebutenolides as reported previously. 6 In addition to the structural confirmation of 8a referring to the literature, 1f the structure of 8n (CCDC No. : 2083287) was further confirmed by single-crystal X-ray crystallography.…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…5 Although DACs with two geminal acceptors are more popularly investigated and used in organic synthesis, we recently found that the synergistic activation of the two vicinal acceptors in DACs can also facilitate the ring-opening transformation of the cyclopropane ring. 6 Importantly, a δ-keto ester unit embedded in the DACs with two vicinal acceptors, i.e., the ketone and ester groups, may be converted to the 2-pyrone skeleton if the cyclopropyl C−C bond between them is selectively cleaved (Scheme 1, a). Although selective scission of such cyclopropyl C−C bond substituted by two vicinal acceptors is electronically unfavored, several elegant pioneering works on Figure 1 Selective bioactive molecules with 2-pyrone unit conversions of DACs with two vicinal acceptors to the 2-pyrones derivatives have been documented.…”
mentioning
confidence: 99%
See 3 more Smart Citations